AGW 609 — Human Resource Management - February 2000 - PPP, Pusat Pengajian Pengurusan (2000)
UNIVERSITI SAINS MALAYSIA MASTER OF BUSINESS ADMINISTRATION Second Semester Examination Academic Session 1999/2000 February 2000 AGW 609 — Human Resource Management Time: [3 hours]